Molecular Identification of Arbuscular Mycorrhizal Fungi in Roots: Perspectives and Problems - Redecker, Dirk; Hijri, Isabelle; Wiemken, Andres (Folia geobotanica, 2003)
Molecular identification methods are about to revolutionize studies on ecology of arbuscular mycorrhiza. These techniques offer the unique opportunity to investigate communities of arbuscular mycorrhizal fungi (AMF) within roots. Recent technical advances are reviewed, discussing their drawbacks and advantages. An experimental approach to analyze AMF communities within roots using a molecular identification method is presented. Sample results from the analysis of trap cultures from a current project are shown.